Editorial: microbiome modulation by rifaximin in severe alcoholic hepatitis. Issue 4 (22nd January 2021) - Youn, Gi Soo; Suk, Ki Tae
Abstract : LINKED CONTENT This article is linked to Kim et al paper. To view these articles, visit https://doi.org/10.1111/apt.16200